New Pathway for Management Studies in China: Exploring Qualitative Research Methods of Business Anthropology - Guang Tian, Robert; Liu, Hongfei; Wang, Yanyu (Edelweiss Applied Science and Technology, 2024)
Through an inventory of the existing literature body on Chinese management studies, this paper attempts to present a critical review of the phenomenon that the management studies in contemporary China over-rely on quantitative research methodology. It endeavors to demonstrate that the nature of scientific research is to innovate by seeking truth and, therefore, should not be restricted by quantitative research methods. Improve the effectiveness of academic analyses, it suggests that the scholars in China need to positively adapt the anthropological methodologies to conduct management studies and enhance the process of the localization of management science in the country. It is designed to broaden the approaches toward Chinese management studies by introducing business anthropological methods to Chinese management scholars. It adopts a comparative and case study methodology to demonstrate the limitations of quantitative methods and illustrate the effectiveness of business anthropological approaches for management studies in the Chinese context. The existing literature body demonstrates that excessive quantitative research approaches are utilized in current management studies, while scholars in China primarily ignore the effectiveness of qualitative methods. The necessity for further understanding qualitative research methods in management studies has been recognized more recently by Chinese scholars. They tend to agree that qualitative and quantitative research methodologies are merely different approaches, while the results are the same. One of the compelling new paths to improving management studies and practices is to apply anthropological research methods so that management theory in China can better explain actual human responses and factors that influence their behaviors. Anthropology has always been employed for practical applications. In addition, anthropological methods can enlarge the approaches to management studies and widen the scope for scholars to conduct their research. The combination of anthropology and management will accelerate the localization of management studies and, accordingly, speed up the systematic establishment of Chinese management theory to promote management practices in modern China. Business anthropology is emerging among some outstanding qualitative research methods in Western management studies. On the other hand, China's management science community is still a little behind in this respect. This paper is a pilot study to elaborate on business anthropology and its contribution to specific areas in management studies, such as marketing management, product design, and entrepreneurship in the Chinese context.